A continuous benchmarking infrastructure for high-performance computing applications - Alt, Christoph; Lanser, Martin; Plewinski, Jonas; Janki, Atin; Klawonn, Axel; Köstler, Harald; Selzer, Michael; Rüde, Ulrich (International Journal of Parallel, Emergent and Distributed Systems, 2024)
For scientific software, especially those used for large-scale simulations, achieving good performance and efficiently using the available hardware resources is essential. It is important to regularly perform benchmarks to ensure the efficient use of hardware and software when systems are changing and the software evolves. However, this can become quickly very tedious when many options for parameters, solvers, and hardware architectures are available. We present a continuous benchmarking strategy that automates benchmarking new code changes on high-performance computing clusters. This makes it possible to track how each code change affects the performance and how it evolves.
Created from Fastlane, Scopus look-up
Keywords: computational homogenization; continuous Benchmarking; Continuous integration; finite elements method; lattice Boltzmann method

Geometrically Resolved Simulation of Upstream Migrating Antidune Formation and Propagation - Kemmler, Samuel; Schwarzmeier, Christoph; Rettinger, Christoph; Plewinski, Jonas; Núñez-González, Francisco; Köstler, Harald; Rüde, Ulrich; Vowinckel, Bernhard (40th IAHR World Congres, 2023)
Periodic structures developed at the interface between fluid flows and granular beds in motion are known as bedforms. Among the different types of bedforms in unidirectional free-surface flows, upstream-migrating antidunes in supercritical or near critical flows are perhaps the most striking features, given their apparently counterintuitive movement in opposite direction to the main flow. Analyzing the mechanisms involved in the formation and propagation of antidunes is necessary to understand their effects on channel roughness, sediment transport capacity and the turbulent flow field of streams, and is also crucial to identify the sedimentological footprint of antidunes for the reconstruction of paleohydraulic flows. However, difficulties to perform flow and sediment transport measurements in laboratory and field under near critical or supercritical flow conditions have precluded a deeper understanding of antidunes. In this regard, simulations using geometrically resolved particles carried out on increasingly powerful supercomputers, offer a viable methodological alternative. Such massively parallelized simulations generate highly resolved flow field data and particle trajectories to analyze the antidune dynamics. These data are crucial to link preferential antidune wavelength, height, celerity and migration direction to a given flow condition. In this work, we present a method for the simulation of antidune formation and propagation with geometrically resolved particles. We use the lattice Boltzmann method (LBM) for the fluid dynamics simulation and extend it with a free-surface model [1], which is a prerequisite for the formation of antidunes. The particle interactions are modeled using a discrete element method with proper momentum exchange for the fluid-particle coupling [2] implemented in the waLBerla framework [3]. This approach allows for large scale antidune simulations consisting of thousands of particles. We aim to provide a direct comparison of our simulation results to the study of Pascal et al. [4], who have investigated the variability of antidune morphodynamics in natural gravel. We will show that our simulation approach is capable to reproduce the key features of antidunes and we will present first results on the antidune dynamics as well as fluid and particle statistics to better understand the mechanisms involved in the formation and propagation of antidunes. To the best of our knowledge, this is the first study in which upstream-migrating antidunes are successfully simulated with a high-resolution model. [1] Schwarzmeier, C., & Rüde, U. (2022). Analysis and comparison of boundary condition variants in the free-surface lattice Boltzmann method. arXiv preprint arXiv:2207.13962. [2] Rettinger, C., & Rüde, U. (2017). A comparative study of fluid-particle coupling methods for fully resolved lattice Boltzmann simulations. Computers & Fluids, 154, 74-89. [3] https://www.walberla.net/ [4] Pascal, I., Ancey, C., & Bohorquez, P. (2021). The variability of antidune morphodynamics on steep slopes. Earth Surface Processes and Landforms, 46(9), 1750-17

Particle-resolved simulation of antidunes in free-surface flows - Schwarzmeier, Christoph; Rettinger, Christoph; Kemmler, Samuel; Plewinski, Jonas; Núñez-González, Francisco; Köstler, Harald; Rüde, Ulrich; Vowinckel, Bernhard (Journal of Fluid Mechanics, 2023)
The interaction of supercritical turbulent flows with granular sediment beds is challenging to study both experimentally and numerically. This challenging task has hampered advances in understanding antidunes, the most characteristic bedform of supercritical flows. This article presents the first numerical attempt to simulate upstream-migrating antidunes with geometrically resolved particles and a liquid–gas interface. Our simulations provide data at a resolution higher than laboratory experiments, and they can therefore provide new insights into the mechanisms of antidune migration and contribute to a deeper understanding of the underlying physics. To manage the simulations’ computational costs and physical complexity, we employ the cumulant lattice Boltzmann method in conjunction with a discrete element method for particle interactions, as well as a volume-of-fluid scheme to track the deformable free surface of the fluid. By reproducing two flow configurations of previous experiments (Pascal et al., Earth Surf. Process. Landf., vol. 46, issue 9, 2021, pp. 1750–1765), we demonstrate that our approach is robust and accurately predicts the antidunes’ amplitude, wavelength and celerity. Furthermore, the simulated wall shear stress, a key parameter governing sediment transport, is in excellent agreement with the experimental measurements. The highly resolved data of fluid and particle motion from our simulation approach open new perspectives for detailed studies of morphodynamics in shallow supercritical flows.<br
Keywords: sediment transport; computational methods

Particle-resolved simulations of antidune migration in supercritical flows - Schwarzmeier, Christoph; Rettinger, Christoph; Kemmler, Samuel; Plewinski, Jonas; Núñez-González, Francisco; Köstler, Harald; Rüde, Ulrich; Vowinckel, Bernhard (EGU General Assembly, 2023)
Antidunes are an important feature in the morphodynamics of streams over steep slopes. These bed forms are short-wave periodic disturbances that develop on the surface of loose granular beds in response to the interaction with supercritical and near-critical shallow, turbulent flows. They arise in fluvial, coastal, and submarine environments and are closely tied to the resulting flow resistance, turbulence, and sediment transport. Antidunes are the only type of bedform that can migrate upstream under the presence of a free surface. This seems counterintuitive and has caught strong interest in hydraulic research. However, up to date little is known about the migration mechanism in connection to turbulence, bed morphology, and sediment transport, because of the challenging supercritical flow conditions, often associated to low submergences. This is in part related to the inherent technical challenges to reproduce rapid flows over an erodible bed in laboratory flumes, as well as to the difficulties to perform non-intrusive measurements. Consequently, experimental data sets in published literature are scarce. Numerical simulations of supercritical flows above an erodible bed can therefore constitute a methodological alternative for the study of antidunes. Such simulations, however, need to properly reflect the interplay of the fluid phase, the sediment particles, and the gas phase above the free surface. In this work we propose to use particle-resolved direct numerical simulations (pr-DNS) in conjunction with a deformable fluid surface to simulate the formation and propagation of upstream migrating antidunes in supercritical flows with high fidelity. We aim to numerically reproduce the experimental campaign recently reported by Pascal et al. (2021), who managed to measure the propagation of upstream migrating antidunes with a high spatial and temporal resolution. For this, we combine the lattice Boltzmann method with the discrete element method to simulate the fluid–particle and particle–particle dynamics (Rettinger & Rüde, 2022) and extend it with a volume of fluid scheme (Schwarzmeier et al., 2023) to track the strongly deformable free fluid surface. The parameter choices of Pascal et al. (2021), with coarse sediment grains and low relative submergence of the particles, allow for a direct overlap of experimental conditions with pr-DNS. In this manner, our simulations successfully close the gap between river morphodynamics experiments and pr-DNS, to couple bedform and free-surface interactions with large-scale simulations consisting of a sediment bed comprising thousands of particles in unidirectional, supercritical turbulent flow

Performance analysis of the free surface lattice Boltzmann implementation in waLBerla - Plewinski, Jonas; Alt, Christoph; Köstler, Harald; Rüde, Ulrich (Proceedings in Applied Mathematics and Mechanics, 2024)
The free-surface lattice Boltzmann method uses a volume of fluid approach to simulate immiscible two-fluid flow problems. It divides the simulation domain into three distinct phases—gas, fluid, and interface—where computation within the gas phase is disregarded. The interface delineates a one-cell-thick layer between the first two phases, validated physically for implementation in the HPC C++ multiphysics framework waLBerla but lacking an exhaustive performance analysis. This paper aims to shed light on node-level performance on different architectures, employing continuous benchmarking, showing and analyzing weak scaling results on a modern HPC cluster, the Fritz supercomputer, and reporting energy consumption for the current implementation.<br